A Study on Clinical Characteristics and Diagnostic Stability in Acute and Transient Psychotic Disorders - Rizwan Farooq, Unaiza Jawad, Imran Khan, Muhammad Shoaib Irfan, Subhan Ullah, Shakil Asif (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: The acute and transient psychotic disorders (ATPDs) as an independent diagnostic entity have become a subject of nosological debate. Numerous studies considered these psychosis as schizophrenia variants or mood disorders leading to diagnostic instability. The present study aimed to investigate the clinical characteristics and diagnostic stability in acute and transient psychotic disorders. Methodology: A total of 45 acute and transient psychotic disorders diagnosed patients were investigated at Psychiatry and Behavioral Sciences LGH Lahore and Psychiatry unit, Khyber Teaching Hospital Peshawar Pakistan for six months duration from 1st June 2021 to 30th November 2021. All the patients with ages ranging from 17 to 65 years fulfilling ATPDs criteria as per ICD-10 were enrolled. The written informed consent form was taken from the patients’ relatives. Patients with drug intoxication, psychotic illness history, brain disorders, mental retardation, and those taking regular antipsychotic treatment were excluded. Patients were followed up for one month and three months and diagnosis was reevaluated after each follow-up. During the follow-up period, global functioning, clinical manifestations, and quality of life were all evaluated on a regular basis. Results: Of the total 45 ATPD diagnosed patients, male and female patients were 18 (40%) and 27 (60%) respectively. Overall mean age was 29.7±7.9 years. After one month follow-up, the prevalence of ATPD, mood disorder, and schizophrenia was 39 (86.7%), 4 (8.9%), and 2 (4.4%) respectively. After 3 months follow-up, the incidence of diagnosed ATPDs, schizophrenia, and mood disorder were 36 (80%), 5 (11.1%), and 4 (8.9%) respectively. About 36 (80%) patients retained ATPDs whereas diagnosis of psychotic disorders changed in 9 (20%) patients. Conclusion: The acute and transient psychotic disorder was diagnostically stable entity. Patient’s sizable proportion of ATPDs initial diagnosis changed to Schizophrenia-related disorders representing early manifestations.